The Study of Public Space From The Sociofugal and Sociopetal Aspect (Case Study: Faculty of Architecture and Design, UPN - Susanti, Wiwik Dwi; M.Pranoto S; Sri Suryani Y.W (Nusantara Science and Technology Proceedings)
There is inner closeness between students and campus, because some students do activities on campus. Public space are the most widely used by students in activities. So, the availability of public space on campus is very necessary. The quantity and quality of public space on campus is a main indicator in shaping student behavior. The purpose of a public space is to support student activities from the academy aspect and soft skill activities. While the availability of public space in the Faculty of Architecture and Design has not been able to provide a maximum container for students both in terms of quality and quantity. In this study try to identify the patterns of public space by using the sociopetal and sociofugal parameters. The concept of sociofugal and sociopetal is an important indicator in testing the quality of public space. Ideally a good public space is dominated by sociofugal aspects because it prioritizes socializing and discussing activities. This study uses architectural methods of behavour mapping which later facilitate the process of observation in the field. Hopefully later with the knowledge gained can contribute ideas for the design of the quality of public space in the future.